Three-dimensional modelling of femur bone using various scanning systems for modelling of knee implant and virtual aid of surgical planning. (July 2019) - Sindhu, V.; Soundarapandian, S.
Highlights: Femur model is needed for implant modeling and surgery. Femur model was obtained using different scanning systems. Models were analyzed qualitatively and quantitatively for finding accurate system. Deviation analysis was done for comparison between the CAD models. X-ray Computed Tomography scanning system gave accurate model than other scanning systems. Abstract: Three-dimensional (3D) bone model is needed for various applications such as anatomical study, implant modelling, and pre-surgical planning. One of the significant challenges which is faced by the scientists and medical doctors is to measure and model the load-bearing joints (knee, hip, shoulder, elbow, etc.) as accurately. Nowadays, Total Knee Replacement (TKR) is the surgery that has been occurring all over the world to bring back the normal life of injured persons or arthritis affected people. TKR is considered as a complex surgery that includes, the removal of cartilage tissue from the part of femur and tibia and reconstruct the surface of entire knee joint with the metallic-based implants. For this, a 3D model of the knee joint (femur and tibia) is necessary to model the relevant implant. Therefore, in this work, a femur was taken as an object to measure its dimensions as more accurately using various scanning systems such as Coordinate Measuring Machine (CMM), 3D laser scanner, X-ray Computed Tomography (CT) and FARO arm edge. While in the measurement process, 3D coordinates of the femur bone were extracted and the data was used to generate the 3D model of the femur. Various Computer Aided Design (CAD) tools were used to generate the 3D model of the femur and further this 3D model can be used to generate the tool paths for aiding the TKR surgery. 3D models of the femur bone generated using various scanning systems were compared using quantitative, qualitative, femoral feature and deviation analyses. It was found that X-ray Computed Tomography scanning systems have given more accurate data for generating the model of femur with minimum error.